Surveillance of the Middle East respiratory syndrome (MERS) coronavirus (CoV) infection in healthcare workers after contact with confirmed MERS patients: incidence and risk factors of MERS-CoV seropositivity. (October 2016) - Kim, C.-J.; Choi, W.S.; Jung, Y.; Kiem, S.; Seol, H.Y.; Woo, H.J.; Choi, Y.H.; Son, J.S.; Kim, K.-H.; Kim, Y.-S.; Kim, E.S.; Park, S.H.; et al.
Abstract: Given the mode of transmission of Middle East respiratory syndrome (MERS), healthcare workers (HCWs) in contact with MERS patients are expected to be at risk of MERS infections. We evaluated the prevalence of MERS coronavirus (CoV) immunoglobulin (Ig) G in HCWs exposed to MERS patients and calculated the incidence of MERS-affected cases in HCWs. We enrolled HCWs from hospitals where confirmed MERS patients had visited. Serum was collected 4 to 6 weeks after the last contact with a confirmed MERS patient. We performed an enzyme-linked immunosorbent assay (ELISA) to screen for the presence of MERS-CoV IgG and an indirect immunofluorescence test (IIFT) to confirm MERS-CoV IgG. We used a questionnaire to collect information regarding the exposure. We calculated the incidence of MERS-affected cases by dividing the sum of PCR-confirmed and serology-confirmed cases by the number of exposed HCWs in participating hospitals. In total, 1169 HCWs in 31 hospitals had contact with 114 MERS patients, and among the HCWs, 15 were PCR-confirmed MERS cases in study hospitals. Serologic analysis was performed for 737 participants. ELISA was positive in five participants and borderline for seven. IIFT was positive for two (0.3%) of these 12 participants. Among the participants who did not use appropriate personal protective equipment (PPE), seropositivity was 0.7% (2/294) compared to 0% (0/443) in cases with appropriate PPE use. The incidence of MERS infection in HCWs was 1.5% (17/1169). The seroprevalence of MERS-CoV IgG among HCWs was higher among participants who did not use appropriate PPE.